IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DALAM MENINGKATKAN KUALITAS PENDIDIKAN DI SEKOLAH DASAR - Syoviana, Elvi; Syam, Fadhli; Hartanto, Hartanto; Putra, Gilang Septiadi; Aripin, Asad Samsul; Hidayat, Haris (Jurnal Dedikasi Pendidikan, 2025)
This research aims to oversee the School Based Management (MBS) initiative to improve the quality and standards of education at SD Islam Plus Daaruth Thullab 03 Sitiung. This research uses a qualitative approach with descriptive methods. Data collection was carried out through interviews, observations and comprehensive documentation involving school principals, teachers, administrative staff and school committees. Research findings show that the implementation of SBM at this institution is effective, facilitated by the active participation of various stakeholders, including parents, teachers and the community in the decision-making process at the school. Strategies used to improve the quality or standards of education include curriculum management, teacher professional development, and administration of facilities and infrastructure. However, there are several challenges, including limited resources and inadequate teacher training, that hinder optimal implementation of SBM. Nevertheless, MBS has been proven to contribute positively in improving the quality of education at SD Islam Plus Daaruth Thullab 03 Sitiung, as seen from the increase in student learning outcomes and quality of learning. This research suggests increased training and better resource allocation to support the successful implementation of SBM on a sustainable basis